A History of Poetics - Richter, Sandra,Azazmah, Jasmin,Jost, Eva,Zenk, Anja (De Gruyter, 2010)
Since the 1990s, following the end of postmodernism, literary theory has lost much of its dynamics. This book aims at revitalising literary theory exploring two of its historical bases: German poetics and aesthetics. Beginning in the 1770s and ending in the 1950s, the book examines nearly 200 years of this history, thereby providing the reader with a first history of poetics as well as with bibliographies of the subject. Particular attention is paid to the aesthetics and poetics of popular philosophy, of the Hegel-school, empirical and psychological tendencies in the field since the 1860s, the first steps towards a plurality of methods (1890-1930), theoretical confrontations during the Nazi-period as well as the rise of formalist and anthropological approaches from the 1930s onwards. All approaches are evaluated regarding their relevance for academia as well as for the general history of education. If possible, international references and contexts of the relevant theories are taken into account. In sum, the analysis not only shows how differentiated historical accounts in the field were but also reflects how current literary theory could move forward through the rediscovery of sunken ideas
10.1515/9783110222456
Keywords: Aesthetics; German / History; Literature / History and criticism / Theory; etc; Poetics / Bibliography; Poetics / History; Aesthetics; Literary Theory; Literaturtheorie; Poetics; Poetik; Ästhetik; Deutsch; LITERARY CRITICISM / European / German